MRNA profiling in ancient blood stains. (December 2017) - Fabbri, M.; Venturi, M.; Talarico, A.; Frisoni, P.; Gaudio, R.M.; Neri, M.
Abstract: In order to test mRNA profiling as a method to identify aged blood stains, this work tested two sets of blood stain samples, 50 and 60 plus-year-old respectively, on three blood specific markers HBB, ALAS2 and CD93, together with two housekeeping genes represented by ACTB and 18S-rRNA. Blood traces were also tested using HemDirect Hemoglobin test (SERATEC ® ) to compare results. Results: showed HBB as a very stable mRNA molecule highly suitable for the detection of old blood stains. HBB give positive results in over 80% of the 60-year-old samples and over 90% of the 50- year-old samples. All membranes were all weakly positive for blood, except for five 60 years back samples. Full STR profiles were accomplished for all blood samples. This finding proves mRNA profiling an effective and alternative way of identifying aged bloodstains.